2021
DOI: 10.1007/s00125-021-05415-5
|View full text |Cite|
|
Sign up to set email alerts
|

Defining the underlying defect in insulin action in type 2 diabetes

Abstract: Insulin resistance is one of the earliest defects in the pathogenesis of type 2 diabetes. Over the past 50 years, elucidation of the insulin signalling network has provided important mechanistic insights into the abnormalities of glucose, lipid and protein metabolism that underlie insulin resistance. In classical target tissues (liver, muscle and adipose tissue), insulin binding to its receptor initiates a broad signalling cascade mediated by changes in phosphorylation, gene expression and vesicular traffickin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
70
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(87 citation statements)
references
References 120 publications
(135 reference statements)
0
70
0
1
Order By: Relevance
“…On the contrary, the flavonoid myricetin up-regulated p-IR, p-IRS1 and p-AKT in the liver of HFD-fed and STZ-induced type 2 diabetic rats by inhibiting the activity and expression of PTP1B, the tyrosine phosphatase that negatively regulates the insulin signal transduction [38]. Notably, the impaired insulin signaling in the liver promotes gluconeogenesis and suppresses glycogen synthesis [32]. In this sense, it has been shown that flavonoids can modulate several genes related to the glucose metabolism through the IRS/PI3K/AKT pathway [39][40][41].…”
Section: Effects Of Flavonoids On Insulin Signaling In T2dmentioning
confidence: 99%
See 2 more Smart Citations
“…On the contrary, the flavonoid myricetin up-regulated p-IR, p-IRS1 and p-AKT in the liver of HFD-fed and STZ-induced type 2 diabetic rats by inhibiting the activity and expression of PTP1B, the tyrosine phosphatase that negatively regulates the insulin signal transduction [38]. Notably, the impaired insulin signaling in the liver promotes gluconeogenesis and suppresses glycogen synthesis [32]. In this sense, it has been shown that flavonoids can modulate several genes related to the glucose metabolism through the IRS/PI3K/AKT pathway [39][40][41].…”
Section: Effects Of Flavonoids On Insulin Signaling In T2dmentioning
confidence: 99%
“…It is a complex metabolic disorder characterized by persistent elevated blood glucose due to the progressive insulin deficiency (beta-cell dysfunction) on the background of insulin resistance [31]. In diabetes, intrinsic genetic and epigenetic factors, as well as extrinsic factors, including circulating levels of lipids, glucose, or amino acids, can disrupt the insulin signaling network in insulinsensitive tissues, leading to insulin resistance [32]. Numerous scientific evidences have revealed that flavonoids may contribute to prevent or ameliorate the insulin resistance in diabetes by their ability to modulate the insulin signaling pathway in classical target tissues such as liver, muscle, and adipose tissue.…”
Section: Effects Of Flavonoids On Insulin Signaling In T2dmentioning
confidence: 99%
See 1 more Smart Citation
“…By using PICRUSt analysis to predict the functional changes of gut microbiota due to their altered compositions and abundances, we observed that GlcN mainly interfered with the glucolipid metabolism and biosynthesis pathways of intestinal floral in HFD-fed mice ( Figures 6A,B ). Among these pathways, glycolysis/gluconeogenesis, lipid biosynthesis protein, and energy metabolism are closely associated with the development of diabetes mellitus ( Kosanam et al, 2014 ; Batista et al, 2021 ; Wang et al, 2021 ). As an effective arthritis inhibitor, GlcN has been proved to suppress the activation of nucleotide-binding oligomerization domain-like receptor containing pyrin domain 3 (NLRP3) inflammasome in mouse and human macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, Kahn and colleagues [8] discuss how most people with disordered glucose metabolism exhibit insulin resistance, rather than insulin deficiency. The authors outline current and evolving concepts of insulin action and insulin resistance, specifically in type 2 diabetes.…”
mentioning
confidence: 99%